ACE gene variants and sarcoidosis in a Finnish population - Lahtela, Elisa; Wennerström, Annika; Pietinalho, Anne; Petrek, Martin; Kolek, Vitezslav; Lokki, Marja-Liisa; Selroos, Olof (Sarcoidosis, vasculitis, and diffuse lung diseases, 2017)
Background: Sarcoidosis is a systemic inflammatory disease with unknown etiology. However, there is a strong evidence of genetic influence in sarcoidosis. Objectives: We wanted to extend our knowledge of the role of the whole ACE gene, not only insertion/deletion (I/D) polymorphism, in a Finnish sarcoidosis population by genotyping the ACE gene region from 5' upstream to the 3' downstream. Methods: We genotyped 29 single nucleotide polymorphisms (SNPs) spanning the ACE gene from 188 sarcoidosis patients (resolved disease, n=90; persistent disease, n=98) and from 150 controls. These SNPs included tag SNP rs4343 for I/D polymorphism. To replicate the study we genotyped 11 of these SNPs from 139 Czech sarcoidosis patients (resolved disease, n=47; persistent disease, n=92) and 176 healthy controls. Results: No association was detected between I/D genotypes and disease susceptibility or prognosis. We found a novel SNP (rs9905945) in the 5'upstream region of the ACE gene to be moderately associated with favourable disease prognosis in Finnish patients [p=0.035, OR=2.034 (95%CI 1.045-3.960)]. However, in the replication study in Czechs, the SNP rs9905945 did not show association with prognosis of sarcoidosis. Conclusions: This study further characterizes genetic distinctions between Finnish sarcoidosis patients with different prognosis and population-specific genotype distribution of ACE variants. Nevertheless it seems that variants in the ACE gene do not considerably influence the course of the disease in Finnish sarcoidosis patients. (Sarcoidosis Vasc Diffuse Lung Dis 2017; 34: 104-114).
Keywords: angiotensin converting enzyme (ACE); sarcoidosis; single nucleotide polymorphism (SNP); prognosis; insertion/deletion (I/D) polymorphism